2010
DOI: 10.1515/jpem.2010.096
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Mucosal Immunity and Upper Respiratory Tract Infections in Girls

Abstract: In this study we examined whether salivary hormones, physical activity and adiposity were correlated with secretory immunoglobulin A (sIgA) and frequency of upper respiratory tract infections (URTI) in 43 early-pubertal and 59 late-pubertal girls. Physical activity was measured using accelerometers and relative body fat was assessed using bioelectrical impendence. Resting saliva samples were obtained between 1500 and 1800hr and assayed for sIgA, cortisol and testosterone. Participants completed a onemonth heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
(47 reference statements)
0
14
2
Order By: Relevance
“…The frequency of URTI during each week was determined using a daily health log as previously described [17, 18]. URTIs were recorded in order to (a) identify those swimmers who may have high levels of sIgA due to a potential URTI, and (b) examine if stress correlates with URTIs independently of sIgA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of URTI during each week was determined using a daily health log as previously described [17, 18]. URTIs were recorded in order to (a) identify those swimmers who may have high levels of sIgA due to a potential URTI, and (b) examine if stress correlates with URTIs independently of sIgA.…”
Section: Methodsmentioning
confidence: 99%
“…The parents and/or participants were asked to return the health log once completed. The total number of days per week with URTI symptoms was then tallied for each participant, with days being counted only if two or more consecutive days of cold or flu symptoms were reported [17, 18]. …”
Section: Methodsmentioning
confidence: 99%
“…It is currently under debate what intrinsic and/or extrinsic environmental factors moderate immunity in children or adults, subsequently influencing the frequency of URTI [23]. Thus far, a few studies have been published regarding the relationship between the level of PA and the frequency of recurrent infections of the respiratory system in children.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, only a few studies have heretofore been published that address this relationship within the pediatric population. Data on study groups including children between seven and 14 years of age [20,21,22,23] did not necessarily support a clear conclusion that PA actually mitigates recurrent respiratory infections. Canadian mechanistic research indicated that children, who spent more time on sport activities and aerobic fitness activities, reported fewer “sick” leaves [20].…”
Section: Introductionmentioning
confidence: 99%
“…The lower levels of salivary IgA following chronic stress have also been associated with an increased incidence of upper respiratory illness (Jemmott and McClelland, 1989), consistent with the exercise-induced stress of long-term training in elite athletes (Walsh et al, 2011). A study of early pubertal (age 8-11 years) and early adolescent girls (age 14-16 years) looked for correlations between salivary cortisol, physical activity, and adiposity and upper respiratory tract infections and salivary S-IgA (Corbett et al, 2010). Higher concentrations of salivary cortisol were associated with lower salivary S-IgA levels only in the early adolescent girls.…”
Section: Association Of Ontogeny Profiles With Diseasementioning
confidence: 99%